The Effect of Group Counseling on the Confidence of Class X MIA-1 Students at SMA Negeri 2 Takalar for the 2019-2020 Academic Year - Arwati Arwati (Universitas Negeri Makassar, 2021)
Education is always related to human development efforts, so one of the determining factors for the success of education is that it depends on the human element, as well as the success of students in overcoming the problem cannot be separated from the supervising teacher and the students themselves who have self-confidence and want to change. This research is a classroom action research with the aim of researching to describe the self-confidence of students in class X MIA-1 SMA Negeri 2 Takalar before and after being given group counseling and to explain the positive effect of giving group counseling on the self-confidence of students in class X MIA-1 SMA Negeri 2 Takalar. Data collection techniques in this study are questionnaires, observations and interviews.The subjects of this study were students of class X MIA-1 SMA Negeri 2 Takalar with a total of 33 people. The instrument used to collect data in this study was a self-confidence questionnaire. The data obtained were then processed and analyzed descriptively and inferentially. Hypothesis testing was carried out using statistical techniques, namely t-test (one tail) at a significant level of 95%.